The political vocation of philosophy - Di Cesare, Donatella 1956- (Polity Press, 2021)
"This book seeks to redefine the purpose of philosophy for our times. Faced with the saturated immanence of the world, philosophy is summoned to return to its original vocation and, after a long absence in which it lost its voice, it is called on to reawaken the community and protect the life we share in common"--
"Originally published in Italian as Sulla vocazione politica della filosofia, 2018 Bollati Boringhieri editore, Torino.
Keywords: Politische Philosophie; Political science / Philosophy; Philosophy